Estudo, proposta de modelo geral de simula??o e implementa??o de modelo espec?fico para ranging inicial em redes IEEE 802.16d - Hernandes, Herlon Clayton Paggi (2007)
Based on studies of the IEEE 802.16 standard and its variants, it was developed a general model that satisfies the specific and common functionalities of the MAC layer as well as for the PHY layer, not only for the radio-base stations, but also for subscriber?s stations. The proposed model organizes main technology functionalities from the point of view of uplink and downlink. From this general model, it was developed and implemented in an event-driven based tool, a specific model that aims to simulate the process of a subscriber's station network entry. This simulator is divided in functional blocks that are called through parameterized events, based on tables and variables, which has the objective to simulate a real communication environment. Using the tool it is possible to visualize the whole process of a subscriber's station network entry. The details of the PHY layer synchronization, MAC synchronization, initial ranging and capabilities negotiation processes, are easily visualized and analyzed. The implementation done serves as subsidy for future works and implementations, once the proposed model it is very flexible and modular.